Therapeutic drug monitoring of antimicrobials. (May 2016) - Balakrishnan, Indran; Shorten, Robert J
As pathology services become more centralized and automated, the measurement of therapeutic antimicrobial drugs concentrations is increasingly performed in clinical biochemistry or 'blood science' laboratories. This review outlines key groups of antimicrobial agents: aminoglycosides, glycopeptides, antifungal agents and antituberculosis agents, their role in managing infectious diseases, and the reasons why serum concentration measurement is important.